The Use of Artificial Intelligence (AI) to Support Student Learning Motivation in the Economics Education Study Program at Muhammadiyah University of Sampit - muhammad firman; M. Hadianur; M. Qahfi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to determine the use of Artificial Intelligence (AI) in supporting the learning motivation of students in the Economics Education Study Program at Muhammadiyah University of Sampit. The study used a qualitative approach with a descriptive research type. The research informants consisted of four students who actively use AI in learning activities and one lecturer as a supporting informant. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model. The results showed that AI was used by students to search for references, understand lecture material, create summaries, and assist in completing academic assignments. The use of AI provides benefits in the form of easy access to information, increased understanding of the material, efficiency of study time, and increased student self-confidence. In addition, AI contributes to increased learning motivation as demonstrated by students' perseverance, independence, and interest in learning. However, excessive use of AI has the potential to cause dependency, so it needs to be balanced with critical thinking skills and digital literacy. Thus, Artificial Intelligence can be an effective learning support tool in increasing student learning motivation.